Analisa Environmental Cost pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2011, 2012 dan 2013 - Kartike Dewi (Bina Nusantara University, 2014)
Environmental damage due to over-exploitation by employers without thinking about environmental improvements result in long-term environmental damage. Allocation of environmental costs, making high expenses on companies that ultimately will reduce net income. This study will examine companies that have great potential to damage the environment, but the company is willing to make the allocation of environmental costs in its income statement, and the company also wants to follow the PROPER program created by the Ministry of Environment for the period 2011 to 2013. The research was conducted using secondary data in www.idx.co.id and www.proper.menlh.go.id. Financial Statements of the company that made the sample examined by checking whether there is environmental damage costs are allocated and check the results of PROPER (Program Performance Rating). This study will determine whether the company identifying, recognizing, measuring and presenting the cost of environmental damage in the Financial Statements. Results obtained from secondary data is that many companies have yet to identify, acknowledge, measure and present the cost of the destruction of nature in the financial statement, the company may have a cost allocation but still use the Incidental Charges account, so that when the pages are checked through www.idx.co.id charge is not visible. It is expected that in the future the company create its own environmental cost allocation account so that it can be easily identified by users of Financial Statements.